De sammansatta orden och ordfogningarna i Mikael Agricola-ordboken - Vaittinen, Tanja; Lehtosalo, Kaisa (Nordiske Studier i Leksikografi, 2010)
Mikael Agricola is the founder of literary Finnish language. During the years 1543–1552 he published nine religious books which are for most parts translations from Latin, Greek, German and Swedish. Although some research has been made of his lexicon, no thorough dictionary has yet been written. The aim of our project is to publish a full lexicon of all the lexemes Mikael Agricola used. This paper presents one of the central challenges we have in constructing lemmas, namely the problem of deciding whether words form compounds or phrases. Mikael Agricola’s language was rich in variation and rather unsystematic, which means he did not always write compound words together as is the rule in modern Finnish. He also seems to have been fond of compound verbs which are valued to be un-Finnish by most researchers. In our study we explain our editorial policies and justify why we include several types of compounds and also phrases as lemmas in our dictionary. It is our view that Mikael Agricola Dictionary should give an honest impression of his language.